Struggles with Dramatic Form in 16th-Century English Biblical Plays - Joanna Matyjaszczyk (Anglica. An International Journal of English Studies)
The aim of the article is to pinpoint how 16th-century biblical drama tried to appropriate its genre and medium to carry the reformist message and in what sense the project turned out to be a self-defeating one. The analysis of selected plays from reformed biblical cycles (The Chester Mystery Cycle, play iv; and “The Norwich Grocers’ Play”) and newly composed drama (John Bale’s plays, Lewis Wager’s Life and Repentaunce of Marie Magdalene, the anonymous “History of Jacob and Esau”), supported with an over- view of the criticism on the matter, reveals some common tensions in the dramatic texts which may have had their roots in the reformist need to eliminate any room for doubt that a theatrical performance could leave. The conclusion is that, in its attempts at striking the right balance between dramatizing and overt sermonizing, engaging and distancing, as well as providing an immersive experience and discouraging it, post-Reformation Scrip- ture-based drama oscillated between being more effective as a performance or as a carrier of the doctrinal message, with the resulting tendency to subvert either the former or the latter.